2018
DOI: 10.1002/jwmg.21492
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use change structures carnivore communities in remaining tallgrass prairie

Abstract: The Flint Hills ecoregion is the largest remaining tract of native tallgrass prairie in North America. Contemporary landscape change (e.g., urbanization, agricultural production) in this region is likely affecting native biodiversity; however, we have a limited understanding of how these changes might affect carnivores. We used camera traps distributed across urban‐rural land‐use gradients, and multiseason occupancy models, to investigate the influence of landscape structure and composition on habitat occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 97 publications
2
18
0
Order By: Relevance
“…However, the 95% CI around the occupancy estimates for each WMU overlapped, making it difficult to ascertain the factors responsible for geographic variation in participant‐level occupancy. Our participant‐level occupancy estimates are similar to those reported for coyotes elsewhere in the midwestern USA using camera traps (Berry, Schooley, & Ward, 2017; Lesmeister et al, 2015; Wait et al, 2018). We suggest that analyzing observational data from citizen scientists within a hierarchical modeling framework that accounts for imperfect detection is a better option for modeling the distribution of cryptic wildlife species compared to estimates of observation per unit effort or area sampled.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the 95% CI around the occupancy estimates for each WMU overlapped, making it difficult to ascertain the factors responsible for geographic variation in participant‐level occupancy. Our participant‐level occupancy estimates are similar to those reported for coyotes elsewhere in the midwestern USA using camera traps (Berry, Schooley, & Ward, 2017; Lesmeister et al, 2015; Wait et al, 2018). We suggest that analyzing observational data from citizen scientists within a hierarchical modeling framework that accounts for imperfect detection is a better option for modeling the distribution of cryptic wildlife species compared to estimates of observation per unit effort or area sampled.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the hierarchical nature of our sampling design (participants with multiple visits nested within counties), we initially modeled our data using a single-season multi-scale occupancy model, which estimates occupancy at both the sample unit scale (the county level) and at the sample station scale (the participant level) (Nichols et al, 2008). However, coyotes were detected in all but two counties in Illinois and preliminary analyses showed that estimated county-level occupancy was 1.00, making coyotes ubiquitous throughout Illinois at the county T A B L E 1 Select land cover proportions and weather data (mean and range) by wildlife management unit (WMU) (Lesmeister, Nielsen, Schauber, & Hellgren, 2015;Wait, Ricketts, & Ahlers, 2018) so will be more likely to occupy areas with high patch density.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We placed cameras on trees at approximately 0.5 m above the ground. We attached bait and lure at approximately 0.5–1 m above the ground on a second tree 2–4 m away from the camera (Wait et al ). We placed bait at this height to keep the bait in the frame while having a substantial portion of foreground visible.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, a conventional modelling approach estimates all model covariates using a single buffer area surrounding study sites (typically denoted by the radius used, e.g., 100 m). For example, for medium to large-bodied urban mammals, 500 or 1000 m buffers are commonly employed (Fidino et al 2016, Wait et al 2018, Monterroso et al 2020. Such a choice is often rooted in expert-knowledge, for example, assuming that a 500 m buffer represents an average home range across many mesocarnivores based on past experience with these species , Moreira-Arce et al 2016).…”
Section: Introductionmentioning
confidence: 99%